Cost effectiveness comparison of pre-fabrication with conventional construction method for RMAF ground defense bunker - Tan, Swee Kok (2010)
Pre-fabrication construction method is not new in Malaysian construction industry yet the utilization of such method still relatively low. Government should conduct thorough study of pre-fabrication method aspects and implement it widely especially for government based projects including national security development projects as well. Pre-fabrication method is a modern construction method that widely use by developed countries and it proven that to be more cost effective and cost saving on the aspect of cost, labor, time, quality and durability. Pilot project of bunker construction in Kuantan Airbase (KAB) has chosen as case study for this research. While data required for this case study was generated from site survey, interview segment and construction cost comparison of prefabrication with conventional bunker construction. The findings showed that none of defense bunkers were fully complied with specifications. Majority of respondents agreed that current construction method caused several problems to RMAF and PWD. Pre-fabrication method was foresees contributed solutions to overcome current problems and furthermore this study identified that pre-fabrication is cost effectiveness for implementation. Recommendations suggested to improve current construction caused problems on site by imposing clear delegations and responsibilities for stakeholders whereas encourage cost information transparency provided by PWD. The primary aim and objectives of this study has been accomplished successfully in which the findings have eliminated uncertainties and arguments on prefabrication method cost effectiveness. Majority of respondents gave a feedback that pre-fabricated bunkers implementation are possibility for mass implementation of prefabricated bunkers in 10th Malaysian Plan in all RMAF Bases. This action will save financial of RMAF defense.